CFD analysis of a hybrid sorption-enhanced membrane reactor for hydrogen production during WGS reaction. (26th October 2017) - Ghasemzadeh, K.; Zeynali, R.; Basile, A.; Iulianelli, A.
Abstract: The main aim of this work is a comprehensive study on a new Hybrid Sorption-Enhanced Membrane Reactor (HSE-MR) concept, in which a Pd-Ag membrane during water gas shift (WGS) reaction was applied. This purpose was performed by integrating both the WGS and CO2 absorption reactions. To avoid the high experimental test costs, for evaluating the HSE-MR performance during WGS reaction, a 2D model based on Computational Fluid Dynamic (CFD) method was developed. The proposed CFD model provides the local information of pressure and component molar fractions for the driving force analysis at unsteady state conditions. The validation of the HSE-MR during WGS reaction was carried out by experimental data and a good agreement between modeling results and experimental data was found. After model validation, the performance of the HSE-MR has been compared with that obtained by both a Pd-Ag MR and a Sorption-Enhanced Reactor (SER). Moreover, the effects of some significant operating parameters, such as reaction temperature, reaction pressure and gas hour space velocity (GHSV), on the performance of the HSE-MR were studied in terms of CO conversion and hydrogen recovery in compared with both MR and SER. The CFD results show that HSE-MR, during WGS reaction, presents better performance with respect to MR and SER. As a special consequence, CFD simulation results also show that the increasing of operating parameters has a positive effects on the HSE-MR performance during WGS reaction. Highlights: The WGS reaction is modeled in a HSE-MR. The CFD model is applied for evaluating the HSE-MR in comparison with SER and MR. The HSE-MR performance is investigated by varying various operating parameters.